2021
DOI: 10.4054/demres.2021.45.7
|View full text |Cite
|
Sign up to set email alerts
|

Gendering health differences between nonmigrants and migrants by duration of stay in Italy

Abstract: BACKGROUNDGender and migrant status are important factors for health. A common finding is that women report poorer health than men and that migrants' health converges with nonmigrants' health as the duration of stay in the host country increases. However, little is known about whether gender differences in health persist within migrant groups and whether the migrant-native health convergence differs by gender, especially in the Italian context. OBJECTIVEThis study aims to include the gender dimension in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 91 publications
1
20
0
1
Order By: Relevance
“…It could also be explained by the economic downturn compounding precarious employment conditions and low socioeconomic status. Certainly, there is evidence that migrant health worsens with longer residence in the host country [44,[75][76][77]. However, in the absence of information about the length of stay, we cannot confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It could also be explained by the economic downturn compounding precarious employment conditions and low socioeconomic status. Certainly, there is evidence that migrant health worsens with longer residence in the host country [44,[75][76][77]. However, in the absence of information about the length of stay, we cannot confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 83%
“…This trend could be related to EU membership for Poland and the Czech Republic in 2004 and for Romania and Bulgaria in 2007. This modified the composition of migration flows to Italy, helped along by strong Italian demand for domestic workers and caregivers [77,78]. Finally, further studies are needed to investigate the socio-structural drivers of the differences in mortality that emerged in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3 The first insight into the presence of an HIE in Italy was provided by Moullan and Jusot (2014), who showed that immigrants' self-assessed health is better compared to natives. Subsequent studies that compare mortality rates or other physical and mental health outcomes between immigrants and Italians confirm the existence of an HIE (Fedeli et al 2015;Pacelli et al 2016) and suggest that it decreases over time (Petrelli et al 2017;Caselli, Loi, and Strozza 2017;Loi et al 2018;Loi and Hale 2019;Campostrini et al 2019;Trappolini and Giudici 2021). Studies on immigrants' health care use report mixed results.…”
Section: The Italian Contextmentioning
confidence: 98%
“…The main explanation for the HIE in the Italian context is generally a positive selection effect in the country of origin (Pacelli et al 2016;Loi et al 2018;Trappolini and Giudici 2021). Some authors suggest that the salmon bias, which generally concerns the re-emigration to the country of origin of elderly and unhealthy immigrants, can also play a role (Pacelli et al 2016;Di Napoli et al 2021).…”
Section: The Italian Contextmentioning
confidence: 99%
See 1 more Smart Citation